ĐIỀU CHỈNH NGỮ NGHĨA ĐỊNH LƯỢNG CỦA GIÁ TRỊ NGÔN NGỮ TRONG ĐẠI SỐ GIA TỬ VÀ ỨNG DỤNG - Minh, Nguyễn Duy (Vietnam Journal of Science and Technology, 2012)
ADJUSTMENT OF QUANTIFIED SEMANTICS OF LANGUAGE VALUES IN HEDGE ALGEBRAS AND APPLICATIONS In apply of the Hedge algebras for solving some practice problems, we use only the language value of k finite depth. With limit of language value depth, we can fully control the quantified semantics of this language value and still preserve their order. From this, we has built up a new mathematical theory for the adjustment of quantitative semantic values and proposed a new hedge algebras reasoning b40y approaching control quantified semantics of the language values ​​by using genetic algorithms and interpolation RBF neural network. The results are applied on the dynamical model of aircraft landing control problem of Ross [5] show that our method is true, effective and can apply for several similar problems.